Unscrambling of the British Empire: India and Pakistan as 'unequal' members of the Commonwealth. Issue 1 (2nd January 2016) - Waseem, Mohammad
ABSTRACT: This article seeks to address the phenomenon of the British Commonwealth diplomacy at a historical juncture of adjustment to the emergent postcolonial reality of India and Pakistan. It focuses on the issue of London's diplomatic correspondence on sharing the confidential information with the old and new dominions. It seeks to explore the nature of the diplomatic dilemma of His Majesty's Government with reference to the 'alien' culture, religion and race of the two South Asian countries on the one hand and the need to keep the Commonwealth as a major instrument of projecting and protecting the British influence on the world stage on the other. The article analyses this duality of purpose in the context of the competing views of London about the nature and quantum of information to be shared with its counterparts in Delhi and Karachi. This debate is couched in the framework of wider currents of global and regional diplomacy characterized by the superpower rivalry and Indo-Pakistan conflict, respectively, that underscored London's reservations about treating the old and new dominions on an equal footing. This article grasps the moment of a global change in power and prestige as the Commonwealth increasingly lost its significance due to the quest of the newly independent countries to operate through their respective regional frameworks as well as emergence of the United Nations as a viable and powerful international organization. This moment defines the two parallel developments of London's unwillingness to trust the two South Asian countries with full diplomatic communication and the latter's gradual drift away from the Commonwealth's core principles of policy.